2009
DOI: 10.3892/ijmm_00000333
|View full text |Cite
|
Sign up to set email alerts
|

Impact of combinatory growth factor application on rabbit Achilles tendon injury with operative versus conservative treatment: A pilot study

Abstract: Abstract. Acute Achilles tendon (AT) rupture is a common injury with a comparatively high complication rate. Presently, surgical treatments compete with nonoperative treatment modalities. The aim of this study was to elucidate the possible beneficial effects of short-term combinatory application of growth factors on tendon healing during operative or conservative treatment. In this controlled laboratory study, the left ATs of 40 adult New Zealand White rabbits were transected and either sutured or treated cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…24 The second important finding of the current study is that conservative treatment of dissected Achilles tendons led to increased length and decreased diameter at the defect site. This finding is supported by a study by Konerding et al, 29 who showed that sutured Achilles tendons were shorter and thicker in appearance, whereas the nonsutured tendons appeared elongated and more slender. Furthermore, nearly identical maximum tensile strengths (median, 245 vs 253.4 N) were reported 3 months after tenotomy in operatively and nonoperatively treated animals.…”
Section: E1386supporting
confidence: 75%
“…24 The second important finding of the current study is that conservative treatment of dissected Achilles tendons led to increased length and decreased diameter at the defect site. This finding is supported by a study by Konerding et al, 29 who showed that sutured Achilles tendons were shorter and thicker in appearance, whereas the nonsutured tendons appeared elongated and more slender. Furthermore, nearly identical maximum tensile strengths (median, 245 vs 253.4 N) were reported 3 months after tenotomy in operatively and nonoperatively treated animals.…”
Section: E1386supporting
confidence: 75%
“…Zhang et al (17) reported the promising effect of vascular endothelial growth factor on rat Achilles tendon repair. Despite these positive findings, Konerding et al (2) studied the effect of short-term application of a combination of growth factors on tendon healing in cases of conservative and operative treatment, and reported that the use of growth factor did not result in a significant biomechanical or histological improvement in collagen type ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Improved Achilles tendon healing is reported using bFGF together with VEGF in a rabbit model where both GFs are coated onto a stabilising mineral nanostructure (Yu et al, 2017). However, in a larger study using 40 rabbits, repeated treatment with VEGF, bFGF and rPDGF (day of surgery and day 3, 5 and 7) does not improve healing under conservative or operative conditions (Konerding et al, 2010).…”
Section: Introductionmentioning
confidence: 99%